2007
DOI: 10.1128/jvi.00479-07
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Maturation Is Sensitive to Functional Inhibition of ESCRT-III, Vps4, and γ2-Adaptin

Abstract: Hepatitis B virus (HBV) is an enveloped DNA virus that presumably buds at intracellular membranes of infected cells. HBV budding involves two endocytic host proteins, the ubiquitin-interacting adaptor ␥2-adaptin and the Nedd4 ubiquitin ligase. Here, we demonstrate that HBV release also requires the cellular machinery that generates internal vesicles of multivesicular bodies (MVBs). In order to perturb the MVB machinery in HBV-replicating liver cells, we used ectopic expression of dominant-negative mutants of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
193
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(202 citation statements)
references
References 45 publications
8
193
0
Order By: Relevance
“…Nevertheless, results from this work showed that Dane's-like particles and SVP localize in different cellular compartments. This is in agreement with recent evidences showing that the viral and subviral HBV assembly pathways seemingly differ in their requirement for cell functions and trafficking routes [25,26] . While HBV virions budding required the involvement of MVB functions, the mechanisms of SVP production showed to be clearly distinct and likely independent of MVB functions [25,26] .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, results from this work showed that Dane's-like particles and SVP localize in different cellular compartments. This is in agreement with recent evidences showing that the viral and subviral HBV assembly pathways seemingly differ in their requirement for cell functions and trafficking routes [25,26] . While HBV virions budding required the involvement of MVB functions, the mechanisms of SVP production showed to be clearly distinct and likely independent of MVB functions [25,26] .…”
Section: Discussionsupporting
confidence: 81%
“…Most of these viruses access the MVB machinery through its virusencoded late assembly domains and bud through the plasma membrane. In addition, recent communications have reported the involvement of MVB functions in HBV virion maturation and egress using virusreplicating liver cell lines [25,26] . HBV virions have been suggested to bud into internal MVB-related compartments and exit the cell by the exosome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A DN ATPase-defective mutant of Vps4, in which the active site glutamic acid has been mutated to glutamine, leads to defective MVB sorting and formation of aberrant endosomes in BHK cells (Bishop & Woodman, 2000) and also in Huh7 cells. Production of infectious particles of HIV-1 (Garrus et al, 2001), HSV-1 (Crump et al, 2007), HBV (Lambert et al, 2007) and ASV (Pincetic et al, 2008) is inhibited upon expression of the Vps4DN protein. The wild-type or DN forms of Vps4, tagged with GFP (Vps4WT-GFP or Vps4DN-GFP) were transfected into Huh7 cells, the distribution of Vps4DN-GFP was distinct from Vps4WT ( Fig.…”
Section: Inhibition Of Vps4 Function Blocks Hcv Particle Productionmentioning
confidence: 99%
“…In the absence of Vps4 activity, the ESCRT complex cannot function and aberrant endosomes are formed. Numerous enveloped RNA viruses such as human immunodeficiency virus type 1 (HIV-1) (Garrus et al, 2001), Ebola virus (Martin-Serrano et al, 2001) and avian sarcoma virus (ASV) (Pincetic et al, 2008) and, more recently, enveloped DNA viruses including hepatitis B virus (HBV) (Lambert et al, 2007) and herpes simplex virus 1 (HSV-1) (Crump et al, 2007) have been shown to utilize ESCRT complexes during virion morphogenesis. In most cases viruses interact with the ESCRT machinery via late (L) domains, short motifs normally found in capsid or matrix proteins, which act as docking sites for ESCRT components.…”
Section: Introductionmentioning
confidence: 99%
“…Positive-sense strand synthesis by viral polymerase and pregenomic mRNA degradation by a ribonuclease follows. The encapsidated viral genome may now be enveloped by a lipid envelope containing embedded HBsAg and be secreted from the host hepatocyte [47][48][49].…”
Section: Viral Life Cyclementioning
confidence: 99%